Emerging research themes in maternal hypothyroidism: a bibliometric exploration - Chen, Ailing; Luo, Zouqing; Zhang, Jinqiu; Cao, Xiaohui (Frontiers in Immunology, 2024)
Background: Hypothyroidism, a prevalent endocrine disorder, carries significant implications for maternal and infant health, especially in the context of maternal hypothyroidism. Despite a gradual surge in recent research, achieving a comprehensive understanding of the current state, focal points, and developmental trends in this field remains challenging. Clarifying these aspects and advancing research could notably enhance maternal-infant health outcomes. Therefore, this study employs bibliometric methods to systematically scrutinize maternal hypothyroidism research, serving as a reference for further investigations.Objective: Through bibliometric analysis, this study seeks to unveil key research focus areas, developmental trends, and primary contributors in Maternal Hypothyroidism. The findings offer insights and recommendations to inform future research endeavors in this domain.Methods: Literature metrics analysis was performed on data retrieved and extracted from the Web of Science Core Collection database. The analysis examined the evolution and thematic trends of literature related to Maternal Hypothyroidism. Data were collected on October 28, 2023, and bibliometric analysis was performed using VOSviewer, CiteSpace, and the Bibliometrix software package, considering specific characteristics such as publication year, country/region, institution, authorship, journals, references, and keywords. Results: Retrieved from 1,078 journals, 4,184 articles were authored by 18,037 contributors in 4,580 institutions across 113 countries/regions on six continents. Maternal Hypothyroidism research publications surged from 44 to 310 annually, a 604.54% growth from 1991 to 2022. The USA (940 articles, 45,233 citations), China Medical University (82 articles, 2,176 citations), and Teng, Weiping (52 articles, 1,347 citations) emerged as the most productive country, institution, and author, respectively. "Thyroid" topped with 233 publications, followed by "Journal of Clinical Endocrinology & Metabolism" (202) with the most citations (18,513). "Pregnancy" was the most cited keyword, with recent high-frequency keywords such as "outcome," "gestational diabetes," "iodine intake," "preterm birth," "guideline," and "diagnosis" signaling emerging themes in Maternal Hypothyroidism. Conclusions: This study unveils developmental trends, global collaboration patterns, foundational knowledge, and emerging frontiers in Maternal Hypothyroidism. Over 30 years, research has predominantly focused on aspects like diagnosis, treatment guidelines, thyroid function during pregnancy, and postpartum outcomes, with a central emphasis on the correlation between maternal and fetal health.